TROPHIC STATUS OF PHYTOPLANKTON AS BIOINDICATOR OF EUTROPHICATION LEVEL OF FLOOD RETENTION PONDS IN SAMARINDA CITY - Rahayu, Ndaruning Tri; Sudrajat, Sudrajat; Hendra, Medi (Jurnal Pendidikan Matematika dan IPA, 2022)
The flood retention pond in the city of Samarinda, is a body of stagnant water (lentik), the flow of water is not so large that it affects the life of the organisms in it. The research was carried out in December 2020 - March 2021 at three stations using the method Purposive sampling. The composition of phytoplankton species consisted of Chlorophyceae, Dictyochophyceae, Cyanophyceae, Bacillariophyceae (Diatom), Euglenophyceae, Dinophyceae, Trebouxiophyceae. There are three classes of phytoplankton with relatively high abundance, namely Chlorophyceae, Cyanophyceae and Bacillariophyceae (Diatoms). At the moment of condition rain the highest species abundance at station 1 was Eutonia sp. from the Bacillariophyceae (Diatom) class, at station 2 the species of Merismopedia punctata from the Cyanophyceae class and at station 3 Merismopedia punctata from class Cyanophyceae. When conditions are not raining, the highest species abundance at station 1 is Eutonia sp. from the Bacillariophyceae (Diatom) class, at station 2 the species of Merismopedia punctata is from the Cyanophyceae class and at station 3 is the Merismopedia punctata species from the Cyanophyceae class. TSI analysis when it rains and does not rain have an average index value ranged from 10,46 "“ 17,79, the eutrophication status is in the Oligotrophic category. The water quality factor that forces the eutrophication status in this pond is related to the relatively high nitrogen (N) and phosphorus (P) nutrients.